Efficacy of autologous platelet-rich fibrin in osseous regeneration after mandibular third molar surgery: A comparative study - K Surekha (Journal of Dr. NTR University of Health Sciences, 2019)
Aims and Objectives: To evaluate the efficacy of soft tissue healing and bone regeneration in mandibular third molar extraction sockets after placement of platelet-rich fibrin (PRF). Patients and Methods: A split-mouth study was carried out in 15 patients requiring extraction of bilateral impacted mandibular third molars. Patients were divided into group I (test group) and II (control group) of 15 sites in each. Results were compared within the parameters of postoperative pain, facial swelling, soft tissue healing and bone density. Radiological assessment of the extraction site was done. Results: This study clearly indicates a definite improvement in the wound healing, decrease in postoperative edema, wound dehiscence, and increase in the bone density, which signifies and highlights the use of PRF certainly as a valid method inducing hard tissue regeneration. Conclusion: The procedure of PRF preparation is simple, cost-effective, and has demonstrated good results.